Review of the Rebuilding Ireland Home Loan scheme - Conor O'Toole; Rachel Slaymaker (The Economic and Social Research Institute (ESRI), 2020)
This report provides a high-level review of the degree to which the Rebuilding Ireland Home Loan (RIHL) has met its objectives. It also scopes the need for ongoing intervention, details who is applying for the scheme and assesses selected operational considerations such as credit risks, funding considerations, and its market impact.
Keywords: 330; Wohneigentumspolitik; Kreditmarkt; Irland